Perbuatan Pidana dan Pertanggungjawaban Pidana Pegawai Bank Badan Usaha Milik Daerah Atas Realisasi Kredit yang Menimbulkan Kerugian Keuangan Negara (Studi Putusan Pengadilan Negeri Medan No. 15/PID.SUS-TPK/2023/PN.MDN dan Putusan Pengadilan Negeri Medan No. 18/PID.SUS-TPK/2023/PN.MDN) - Rozak, Meirossa Taradita; Ekaputra, Mohammad; Mulyadi, Mahmud (Universitas Batanghari Jambi, 2026)
Issues concerning non-performing loans in government-owned banks (BUMN/BUMD Banks) are frequently framed as acts of corruption by attributing the problem to errors committed by bank employees in conducting credit analysis and/or credit realization, and by linking such errors to the financial resources of BUMN/BUMD banks originating from separated state assets. This study aims to examine the procedures for credit realization in banks, the relationship between banking crimes and corruption in relation to credit realization in BUMD banks and the corresponding criminal liability, as well as to analyze the Medan District Court Decisions No. 15/Pid.Sus-TPK/2023/PN.Mdn and No. 18/Pid.Sus-TPK/2023/PN.Mdn. The research method employed is normative juridical, with data collected through literature study. The findings indicate that credit realization procedures in banks are governed by the Banking Law, Banking Principles, and each bank’s internal regulations. Errors committed by BUMD bank employees in conducting credit analysis which are deemed to deviate from internal regulations, as examined in Medan District Court Decisions No. 15/Pid.Sus-TPK/2023/PN.Mdn and No. 18/Pid.Sus-TPK/2023/PN.Mdn, are not appropriately categorized as acts of corruption, given that other areas of law—namely civil law—remain applicable, thus invoking the ultimum remedium principle of criminal law. Furthermore, even if civil law cannot be applied, the conduct of the BUMD bank employees in question would be more appropriately classified as banking crimes in accordance with the lex specialis systematische principle. Consequently, the imposition of criminal liability for corruption is inappropriate; instead, criminal liability should more properly be directed toward banking crimes.